2014
DOI: 10.1210/jc.2014-2585
|View full text |Cite
|
Sign up to set email alerts
|

Low Testosterone Concentration and Atherosclerotic Disease Markers in Male Patients With Type 2 Diabetes

Abstract: Low T is associated with more advanced atherosclerotic disease markers in middle-aged patients with T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…Our findings in community-dwelling men are consistent with several smaller studies of middle-aged men with symptomatic low T concentrations [10], men with Type 2 diabetes [12,26], in overweight and obese glucose tolerant young men [27], and in healthy middle-aged men [28]. These studies showed an inverse association between T [10,12], free T [26,27] and bioavailable T [28] with CIMT.…”
Section: Associations Of Sex Hormones With Carotid Plaquesupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings in community-dwelling men are consistent with several smaller studies of middle-aged men with symptomatic low T concentrations [10], men with Type 2 diabetes [12,26], in overweight and obese glucose tolerant young men [27], and in healthy middle-aged men [28]. These studies showed an inverse association between T [10,12], free T [26,27] and bioavailable T [28] with CIMT.…”
Section: Associations Of Sex Hormones With Carotid Plaquesupporting
confidence: 91%
“…However, these associations between T and preclinical carotid atherosclerosis are not present in men with established premature CAD. Given the heterogeneity of previously studied cohorts, our results using LC-MS in two distinct and carefully phenotyped cohorts of men of comparable age may explain previous inconsistencies in the literature [10][11][12][13][14][15][26][27][28].…”
Section: Associations Of Sex Hormones With Carotid Plaquementioning
confidence: 84%
See 2 more Smart Citations
“…The study of Schneider HJ et al (12) concluded that obesity, metabolic syndrome, and acute inflammation was associated with hypogonadal testosterone levels. In the study by Javier M. F. et al, (13) hsCRP levels were 2.74 +/-1.37 mg/dL in low serum T group and 0.89 +/-0.93 mg/dL in the normal Serum T group.…”
Section: Testosterone and Hscrpmentioning
confidence: 86%